Crizotinib in the treatment of non-small-cell lung cancer[Polish version: Kryzotynib w leczeniu chorych na niedrobno komórkowego raka płuca p. 485] - Płużański, Adam; Piórek, Aleksandra; Krzakowski, Maciej (Contemporary Oncology/Współczesna Onkologia, 2012)
Recent studies have demonstrated the benefit of EGFR tyrosine kinase inhibitors in the treatment of advanced non-small-cell lung cancer (NSCLC). The role of activation of the anaplastic lymphoma kinase (ALK) pathway and the presence of the fusion gene EML4-ALK are new molecular targets in studies into the pathogenesis and treatment of NSCLC. ALK gene rearrangement is observed in 3–5% of NSCLC patients. Crizotinib is an oral inhibitor of ALK kinase activity, approved for the treatment of NSCLC patients with ALK gene rearrangement. Crizotinib treatment has resulted in a progression-free survival of 7–10 months with 50–60% objective response rate. The present paper gives an overview of literature reports on the role of crizotinib in the treatment of NSCLC patients harbouring a molecular defect in the ALK gene. Molecular diagnosis of ALK-associated aberrations, results of clinical trials of different phases assessing the efficacy and safety profile of crizotinib are also discussed. Attention is given to the likely causes of drug resistance and management strategies in patients with treatment failure.